Measuring the Informal Economy in the Caucasus and Central Asia - Abdih, Yasser; Medina, Leandro (Washington, D.C. : International Monetary Fund, 2013)
This study estimates the size of the informal economy, and the relative contribution of each underlying factor, for the Caucasus and Central Asia countries in 2008. Using a Multiple Indicator-Multiple Cause model, we find that a burdensome tax system, rigid labor market, low institutional quality, and excessive regulation in financial and products markets are determinant factors in explaining the size of the informal economy, which ranges from 26 percent of GDP in Kyrgyz Republic to around 35 percent of GDP in Armenia. Furthermore, the results show that higher levels of informality increase the levels of self employment and the percentage of currency held outside the banking system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet